Genome-Wide Identification of Long Non-Coding RNAs and Their Potential Functions in Poplar Growth and Phenylalanine Biosynthesis - Zhang, Lei; Ge, Xiaolan; Du, Jiujun; Cheng, Xingqi; Peng, Xiaopeng; Hu, Jianjun (Frontiers in Genetics, 2021)
Poplar is an important bioenergy tree species, lncRNAs play important roles in various biological regulatory processes, and its expression pattern is more tissue-specific than mRNA. In this study, P. deltoides ‘Danhong’ (Pd) and P. simonii ‘Tongliao1’ (Ps) with different growth rates and wood quality were used as experimental materials, and the transcriptomes of their shoot apical meristem, xylem, and phloem were sequenced. Furthermore, high-throughput RNA sequencing analysis revealed that the expression patterns of genes and lncRNAs are different between the two genotypes. 6, 355 lncRNAs were identified. Based on targets prediction, lncRNAs and target genes involved in ADP binding, oxidoreductase activity, phenylpropanoid biosynthesis, and cyanoamino acid metabolism. The DElncRNAs in two poplars were co-expressed with transcription factors and structural genes of lignin and flavonoid pathways. In addition, we found the potential target lncRNAs of miRNA. This result provides basic evidence for a better understanding of the regulatory role of lncRNAs in regulating phenylalanine molecular pathways and wood formation.